A Modelling Study by Response Surface Methodology (RSM) on Turbidity Removal Optimization using Nanocellulose Filter Paper (Neolamarckia Cadamba) - Ismail, Nurul Aienna; Hamid, Nor Hazren Abdul (Journal of Advanced Industrial Technology and Application, 2021)
This study observed the influence of initial turbidity, pH and initial temperature on the turbidity removal from the textile wastewater using nanocellulose filter paper from Neolamarckia Cadamba. Response Surface Methodology (RSM) model was employed to optimize and create a predictive model to evaluate the turbidity removal performance on the nanocellulose filter paper. The performance of the RSM model was statistically evaluated in terms of coefficient of determination, R2. The optimum value of turbidity removal of 99.39% were found at 66 NTU, pH 6.4 and 35.9Â°C. The value of prediction that obtained from modelling (RSM) was in agreement with the experimental values with R2 = 88.23%, AAD = 6.87% and RMSE = 0.18 towards the efficiency of turbidity removal